Cost effectiveness and impact on quality of life of abobotulinumtoxinA and onabotulinumtoxinA in the treatment of children with lower limb spasticity in Canada. (2nd June 2020) - Johnston, Karissa; Danchenko, Natalya; Hansen, Ryan; Dinet, Jerome; Liovas, Anna; Armstrong, Ava; Bains, Savreet; Sullivan, Sean D.
Abstract: Background: Injectable botulinum neurotoxins are a mainstay of treatment for pediatric spasticity. AbobotulinumtoxinA and onabotulinumtoxinA are both injectable toxin therapies used to treat pediatric lower limb (PLL) spasticity in Canada. The objective of this study was to assess the cost-effectiveness of abobotulinumtoxinA vs. onabotulinumtoxinA in the treatment of PLL spasticity in Canada. Methods: A probabilistic Markov cohort model with a 2-year time horizon was developed, with health states defined by response to therapy, as characterized by the goal attainment scale (GAS). Based on randomized controlled trial evidence, response to therapy was similar or higher for abobotulinumtoxinA relative to onabotulinumtoxinA; uncertainty was incorporated into model parameters, however, as the two therapies have not been compared head-to-head. Canadian resource use and cost data were incorporated. Results: In the base case, abobotulinumtoxinA generated 1.48 quality-adjusted life years over the model time horizon, compared to 1.47 for onabotulinumtoxinA. AbobotulinumtoxinA was associated with cost savings of 123 CAD, reflecting lower costs in both medication acquisition and health services. The estimated improvement to quality of life and reduced costs result in an estimate of economic dominance for abobotulinumtoxinA over onabotulinumtoxinA. This dominant result persisted across probabilistic and scenario analyses. Key points for decision makers: Based on a review of available clinical evidence, abobotulinumtoxinA was found to have significant and/or numerical efficacy benefits to onabotulinumtoxinA on functional outcomes (Goal Attainment Scale) and tone (Modified Ashworth Scale) and in the treatment of pediatric lower limb spasticity In this cost-effectiveness analysis, abobotulinumtoxinA was found to be associated with greater quality-adjusted life years and lower costs than onabotulinumtoxinA (economically dominant) A limitation of this analysis was the uncertainty around key parameters. Specifically, the lack of head-to-head comparison data for the two therapies, and variable data regarding likely onabotulinumtoxinA dosing in PLL in clinical practice. However, across a range of plausible scenarios, the economic dominant result remained.